2015
DOI: 10.1103/physrevb.92.214110
|View full text |Cite
|
Sign up to set email alerts
|

In situspectroscopic study of the plastic deformation of amorphous silicon under nonhydrostatic conditions induced by indentation

Abstract: Indentation-induced plastic deformation of amorphous silicon (a-Si) thin films was studied by in situ Raman imaging of the deformed contact region of an indented sample, employing a Raman spectroscopy-enhanced instrumented indentation technique. Quantitative analyses of the generated in situ Raman maps provide unique, new insight into the phase behavior of as-implanted a-Si. In particular, the occurrence and evolving spatial distribution of changes in the a-Si structure caused by processes, such as polyamorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
(165 reference statements)
2
18
0
Order By: Relevance
“…However, the difference is small, and there is a non negligible dispersion for S SiNP values. From nanoindentation experiments on a-Si films, Gerbig et al observed the formation of high-density a-Si or of the ordered β-tin phase, characterized by sixfold coordinated atoms, for contact stresses greater than 8.2 GPa [31]. In the present work, larger yield stress values are obtained in all cases.…”
Section: Resultssupporting
confidence: 54%
“…However, the difference is small, and there is a non negligible dispersion for S SiNP values. From nanoindentation experiments on a-Si films, Gerbig et al observed the formation of high-density a-Si or of the ordered β-tin phase, characterized by sixfold coordinated atoms, for contact stresses greater than 8.2 GPa [31]. In the present work, larger yield stress values are obtained in all cases.…”
Section: Resultssupporting
confidence: 54%
“…[1,2] In the literature, one can find evidence that processing conditions like deposition temperature, pressure, and flow rate of gases and processes like etching, chemical treatments, or ion implantation are known to affect the microstructural features as well as the distribution of volume and surface defects in this material. [3][4][5] To gain a deeper understanding between processing-structure-property-performance relationship for a-Si, much recent research interest has focused on characterizing hardness, Young's modulus, and pressure-induced phase transformations measured, i.e., by nanoindentation. [3,[5][6][7] This measurement method is particularly dedicated and successfully applied for studying of mechanical properties of thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers developed in-situ Raman measurement system during indentation, and reported the spatial distribution of crystalline phases during pressureinduced transformations of crystalline silicon under a conospherical diamond indenter, 10) and the spatial distribution of five-fold coordinated silicon atoms in amorphous silicon under the indenter. 11) Although these are important pioneering works on in-situ structural changes in material under an indenter, there is no information on structural changes of oxide glass under a sharp diamond indenter.…”
Section: Introductionmentioning
confidence: 99%